Knowledge, Attitude and Practice of COVID 19 and the factors influencing them among a Rural Population in South India - Osborn, Jenit; Priya, Kamakshi; Satheesh, T; Sudha Ramalingam (Indian Journal of Community Health, 2021)
Background: Mitigation measures to control the novel coronavirus disease 2019 (COVID-19) depends on the public adherence to preventive measures which is influenced by their knowledge and attitude. Aim: To find the knowledge, attitudes and practices (KAP) of the rural population toward COVID-19 and to establish its socio-demographic influencing factors. Material and methods: KAP study regarding Covid-19 was done among the rural population during August 2020 using a semi-structured questionnaire. Results: Among 500 participants, the mean knowledge, attitude and practice score was 21.55± 2.9 ( Range 0- 30 ), 30.0± 2.88 ( Range 12- 36 ) 9.4± 1.25 ( Range 0-13 ) respectively. Higher knowledge was associated with higher education and employed individuals. Favourable attitude was among those aged <35 years and having higher education. Optimistic practices were exhibited by employed individuals and when children <12 years are present in their home. Conclusions: Study participants preceded good knowledge, positive attitude towards COVID-19 but practice is not sufficient enough to win the battle against the dreadful disease due to considerable knowledge- practice gap.